The Systemic Drivers of Gender-Based Violence in Nepal: A Multi-Sectoral Analysis with a Focus on Healthcare System Responses and Gaps - Adhikari, Hom Prasad; Koirala, Sharmila; Singh Shahi, Swati; Regmi , Shilpa; Silwal, Suja (NPRC Journal of Multidisciplinary Research, 2025)
Background: GBV remains one of the most pervasive public health, human rights, and social challenges in Nepal. The prevalence of GBV, despite established legal frameworks, is driven by deep-seated systemic factors that perpetuate inequality and violence against women and marginalized genders. Objective: This paper aims to identify and synthesize the key determinants of GBV in Nepal and provide a comprehensive understanding of the root causes of GBV to inform effective multi-sectoral interventions. Methods: A literature review was conducted of relevant peer-reviewed articles from 2018 through 2025 in academic databases such as Google Scholar, Semantic Scholar, and PubMed. Supplemental information was obtained from reports provided by government agencies and international organizations such as UNFPA and CEDAW. Findings: A number of interrelated primary determinants are identified, including: (1) deep-seated sociocultural and patriarchal norms that entrench male dominance, (2) economic dependence and financial disempowerment of women, (3) disparities in education and awareness of rights, (4) behavioral factors, primarily alcohol consumption, as a significant trigger, and (5) weak law enforcement and institutional response that fosters impunity. Conclusion: The root causes of GBV in Nepal are multilayered, triggered by a synergistic effect of structural, cultural, and economic factors. Finally, effective prevention necessitates dealing with the very basic level of gender inequality on which these determinants rest. Implementation: Key recommendations include integrating gender equality into school curricula, scaling up economic empowerment programs, improving gender-sensitive training for law enforcement and the judiciary, and mounting nationwide campaigns to challenge harmful social norms.